Lipid-Chaperone hypothesis: a common molecular mechanism of membrane disruption by intrinsically disordered rroteins - Sciacca, Michele Federico; Lolicato, Fabio; Tempra, Carmelo; Scollo, Federica; Sahoo, Bikash R.; Watson, Matthew D.; García-Viñuales, Sara; Milardi, Danilo; Raudino, Antonio; Lee, Jennifer C.; Ramamoorthy, Ayyalusamy; La Rosa, Carmelo (ACS chemical neuroscience, 2020)
An increasing number of human diseases has been shown to be linked to aggregation and amyloid formation by intrinsically disordered proteins (IDPs). Amylin, amyloid-β, and α-synuclein are, indeed, involved in type-II diabetes, Alzheimer’s, and Parkinson’s, respectively. Despite the correlation of the toxicity of these proteins at early aggregation stages with membrane damage, the molecular events underlying the process is quite complex to understand. In this study, we demonstrate the crucial role of free lipids in the formation of lipid-protein complex, which enables an easy membrane insertion for amylin, amyloid-β, and α-synuclein. Experimental results from a variety of biophysical methods and molecular dynamics results reveal that this common molecular pathway in membrane poration is shared by amyloidogenic (amylin, amyloid-β, and α-synuclein) and nonamyloidogenic (rat IAPP, β-synuclein) proteins. Based on these results, we propose a “lipid-chaperone” hypothesis as a unifying framework for protein-membrane poration.
Gesehen am 24.02.2021